Therapeutic Mesenchymal Stem/Stromal Cells: Value, Challenges and Optimization - Najar, Mehdi; Melki, Rahma; Khalife, Ferial; Lagneaux, Laurence; Bouhtit, Fatima; Moussa Agha, Douaa; Fahmi, Hassan; Lewalle, Philippe; Fayyad-Kazan, Mohammad; Merimi, Makram (Frontiers in Cell and Developmental Biology, 2022)
Cellular therapy aims to replace damaged resident cells by restoring cellular and molecular environments suitable for tissue repair and regeneration. Among several candidates, mesenchymal stem/stromal cells (MSCs) represent a critical component of stromal niches known to be involved in tissue homeostasis. In vitro, MSCs appear as fibroblast-like plastic adherent cells regardless of the tissue source. The therapeutic value of MSCs is being explored in several conditions, including immunological, inflammatory and degenerative diseases, as well as cancer. An improved understanding of their origin and function would facilitate their clinical use. The stemness of MSCs is still debated and requires further study. Several terms have been used to designate MSCs, although consensual nomenclature has yet to be determined. The presence of distinct markers may facilitate the identification and isolation of specific subpopulations of MSCs. Regarding their therapeutic properties, the mechanisms underlying their immune and trophic effects imply the secretion of various mediators rather than direct cellular contact. These mediators can be packaged in extracellular vesicles, thus paving the way to exploit therapeutic cell-free products derived from MSCs. Of importance, the function of MSCs and their secretome are significantly sensitive to their environment. Several features, such as culture conditions, delivery method, therapeutic dose and the immunobiology of MSCs, may influence their clinical outcomes. In this review, we will summarize recent findings related to MSC properties. We will also discuss the main preclinical and clinical challenges that may influence the therapeutic value of MSCs and discuss some optimization strategies.